TAX PLANNING AND ITS LEGALITY - Saswati, Riniadi; Syafi'i, M. (YURIS: Journal of Court and Justice, 2022)
Paying taxes is the duty of every citizen, within the framework of participation in nation to build the obedience in paying tax. However, on the other hand, as citizens (taxpayers) will miss some of the "wealth". Therefore, how taxpayers remain obedient in carrying out tax obligations within the minimum tax burden Planning is a tool that allows the taxpayer to provide a minimum tax payment plan. Tax planning means planning each event and transaction which supported by its accounting policies in order to reduce the tax burden in minimized amount. Furthermore, it did not violate the tax laws.